Security analysis and market making - Chung, Kee H.; Cho, Seong-Yeon (Journal of Financial Intermediation, 2005)
In this paper we analyze the interrelatedness of security analysis and market-making activities. Our results indicate that there exists a bidirectional and positive relation between analyst following and the number of market makers. Using detailed data on analyst and dealer affiliations, we also find that dealers are more likely to make markets in stocks that are tracked by analysts who are affiliated with the same company. Similarly, analysts follow and issue earnings forecasts more proactively for stocks that are handled by affiliated market makers. We interpret these results as evidence that analysts and market makers work as a team to benefit the company. We discuss a possible conflict of interest between investors and brokerage firms that arises from this collaborative endeavor between analysts and dealers.